Problems of Biodiversity Management in Indonesia (Biodiversitas Journal of Biological Diversity, 2016)
Indonesia is an archipelago of 17.508 islands with land width of 1.9 millions km2 and sea of 3.1 millions km2, having many types of habitat and become one of biodiversity center in the world. There are about 28.000 plants species, 350.000 animals species and about 10.000 microbes predicted lived endemically in Indonesia. The country that represents only 1.32% of the world having 10% of total flowering plants, 12% of mammals, 16% reptiles and amphibian, 17% birds, 25% fishes and 15% of insects in the world. Most of the biodiversity were not investigated and utilized yet. The direct use of the biodiversity is not any risk, and in addition, between government, society and industries sometime does not have the same view and attitude. Habitat destruction and over-exploitation have caused Indonesia having long list of endangered species including 126 birds, 63 mammals and 21 reptiles. The extinction of some species occurred just few years ago like trulek jawa (Vanellus macropterus), insectivore bird (Eutrichomyias rowleyi) in North Sulawesi, and tiger sub species (Panthera tigris) in Java and Bali. It seems that now is time for all Indonesians to introspect and look for the way that can be used for preserving biodiversity.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKeywords: biodiversity, Indonesia, endangered species